Azygos Vein Z Scores in Healthy Fetuses and Fetuses With Venous Malformations Related to the Azygos Vein. (13th October 2016) - Wu, Li-Hong; Xie, Hong-Ning; Paladini, Dario; Zheng, Ju; Du, Liu; Lin, Mei-Fang
Abstract : Objectives: To establish fetal azygos vein and descending aorta sonographic Z score formulas based on femur length and gestational age and to determine the value of azygos vein diameter variation for potential use in the diagnosis of fetal venous malformations related to the azygos vein. Methods: A total of 452 healthy singleton fetuses and 25 fetuses with venous malformations related to the azygos vein underwent prenatal sonography in this retrospective study. Azygos vein and descending aorta diameters were measured offline after spatiotemporal image correlation volume acquisition. Normal azygos vein and descending aorta Z score formulas were constructed for these measurements based on femur length by performing standard regression analysis followed by weighted regression of absolute residual values. The azygos vein‐to‐descending aorta ratio was calculated. Three parameters were compared between venous malformations related to the azygos vein and healthy fetuses. Results: Azygos vein and descending aorta Z score formulas were constructed. Both showed a positive linear correlation with femur length ( r = 0.79 and 0.90, respectively; P < .01) and gestational age ( r = 0.79 and 0.91; P < .01). The azygos vein Z scores and azygos vein‐to‐descending aorta ratios of fetuses with malformations were significantly higher than those of healthy fetuses ( P < .01). In the abnormal group, 96.0% of azygos vein Z scores (24 of 25) were greater than ±2, and 96.0% of azygos vein‐to‐descending aorta ratios (24 of 25) were greater than the 95% confidence interval. Conclusions: The azygos vein Z score formulas we developed can provide a quantitative basis for prenatal screening of venous malformations related to the azygos vein. Azygos vein dilatation and an abnormal azygos vein‐to‐descending aorta ratio may contribute to increasing the recognition of venous malformations involving the azygos vein.